Volunteers in the EFL classroom: supporting public institutions in Ecuador - Borja Román, María José (2024)
This article highlights the work of North American Volunteers carried out through international organizations in the classrooms of five Public High Schools in the Ecuadorian Pacific Coast. The aim of this article is to provide more information to the scarce existing one and provide outcomes and supporting literature that focusses on the work performed by volunteers. A descriptive and qualitative research was carried out through non-participant observation. Five English classes in which volunteers supported Ecuadorian teachers were observed. This data was analyzed and reported, concluding that it is an assistance that students enjoy, and teachers support, since they agree that exposure to a native speaker helped learners with the pronunciation and practice of spoken language.